2019
DOI: 10.5194/gmd-12-541-2019
|View full text |Cite
|
Sign up to set email alerts
|

Global aerosol modeling with MADE3 (v3.0) in EMAC (based on v2.53): model description and evaluation

Abstract: Abstract. Recently, the aerosol microphysics submodel MADE3 (Modal Aerosol Dynamics model for Europe, adapted for global applications, third generation) was introduced as a successor to MADE and MADE-in. It includes nine aerosol species and nine lognormal modes to represent aerosol particles of three different mixing states throughout the aerosol size spectrum. Here, we describe the implementation of the most recent version of MADE3 into the ECHAM/MESSy Atmospheric Chemistry (EMAC) general circulation model, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(91 citation statements)
references
References 165 publications
(198 reference statements)
5
86
0
Order By: Relevance
“…4b. Figure 5 shows the comparison of the annual surface concentrations of CO, O 3 , and NO 2 between IAP-AACM and HTAP CTMs, including CAM-Chem (Lamarque et al, 2012), Oslo CTM3 (Søvde et al, 2012), and CHASER (Sudo et al, 2002). Overall, the global surface CO simulation of the IAP-AACM is lower than the observations, especially in natural source regions.…”
Section: Trace Gasesmentioning
confidence: 96%
“…4b. Figure 5 shows the comparison of the annual surface concentrations of CO, O 3 , and NO 2 between IAP-AACM and HTAP CTMs, including CAM-Chem (Lamarque et al, 2012), Oslo CTM3 (Søvde et al, 2012), and CHASER (Sudo et al, 2002). Overall, the global surface CO simulation of the IAP-AACM is lower than the observations, especially in natural source regions.…”
Section: Trace Gasesmentioning
confidence: 96%
“…In this paper, we describe and evaluate the implementation of a new two-moment cloud microphysical scheme (Kuebbeler et al, 2014) into the global model EMAC (ECHAM/MESSy Atmospheric Chemistry; Jöckel et al, 2010) and its coupling to the aerosol microphysics submodel MADE3 (Modal Aerosol Dynamics model for Europe adapted for global applications, third generation; Kaiser et al, 2019) submodel. The new cloud scheme is based on a previous scheme by Lohmann and Hoose (2009) already available in EMAC, but it now includes the parameterization of aerosol-induced cirrus cloud formation by Kärcher et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…Their resulting estimates of the radiative forcing from various emission sources show a potentially large impact of aerosolinduced cirrus modifications on climate, although other studies (Hendricks et al, 2011;Gettelman and Chen, 2013) found no statistically significant effects. The compelling need for additional insights into this issue motivated the extension of MADE3 towards a better resolved representation of INP properties (Kaiser et al, 2019) and the coupling to a new cloud scheme with a detailed parameterization for aerosol-induced ice formation in cirrus clouds, which is described in the present paper. Since, as discussed above, experimental support for the ice-nucleating properties of BC are still very limited, the modeling tools need to be designed in such a way that different assumptions can be flexibly and efficiently assessed by means of sensitivity studies, in order to explore the parameter space and provide a more precise uncertainty estimate for the resulting effects on climate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparisons are supported with determination of the veracity of emissions data and meteorological observations. The chemical transport modeling can be extended to global averages over time and space constraints relevant to long-term phenomena; these are not discussed here, but are accessed in other venues [250][251][252].…”
mentioning
confidence: 99%